RP-HPLC method development and validation of citalopram in pharmaceutical dosage form - A.Yasodha; Sumayya Shahnaz; G.Venkataih; A.Sivakumar (International Journal of Pharmacy and Analytical Research, 2022)
A simple, sensitive, precise and Reverse phase high performance liquid chromatographic method has been developed for the quantitative analysis of Citalopram drug present in drug substance. A suitable HPLC having a gradient system equipped with manual injector, UV detector is used for this work. The HPLC separation was achieved on HITACHI L2130 with D Elite 2000 software with Isocratic with UV-Visible detector (L2400).C18 Develosil ODS HG-5 RP 150 mm x 4.6 mm 5 µm particle size and column temperature 25ºc used as stationary phase. The mobile phase used in this analysis consists of a mixture of Phosphate Buffer 0.01M potassium dihydrogen phosphate (pH adjusted to 3.0 with ortho phosphoric acid ) and acetonitrile in the ratio of 60:40. Stock sample is prepared by using acetonitrile. Working sample used is about 10 ppm. Flow rate maintained is about 1.0 ml/minute and wavelength is about 229nm. Sample colour is ambient. Injection volume injected about 20 µL with run time 10 minutes. The proposed method provided linear responses within the concentration range 10 ppm for Citalopram LOD and LOQ values for the active substance were 0.04 and 0.12 µg/mL respectively. Regression equations for the drug substance is about 0.994 in all cases. The precision of the method was demonstrated using intraday and inter day assay % RSD values which were in acceptance limit (≤ 2%) in all instances. The proposed method was found to be accurate, precise, reproducible and specific and it can also be used for routine quality control analysis.